Case Study On Luster Industries Berhad - Hin, Ong Chen (2004)
The principal activities of Luster are manufacturing of precision plastic parts and components, PCBA, sub assembly and full assembly of plastic parts and components; and investment holdings. This paper traces the history of Luster, the internal and external environments which it operates, its strengths, weaknesses, opportunities and threat and finally the proposed strategies to be employed in its core competencies to reposition itself in the plastic injection moulding industry.